1990
DOI: 10.1017/s0043174500056034
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Basis for the Different Phloem Mobilities of Chlorsulfuron and Clopyralid

Abstract: Foliar-applied clopyralid was translocated much more readily than chlorsulfuron in the phloem of Tartary buckwheat plants. This result was not due to greater penetration of clopyralid into the treated leaf or to greater retention of chlorsulfuron in the cuticle. Experiments with excised leaf disks indicated that chlorsulfuron was taken up more readily by the leaf tissue and accumulated in the tissue to a higher concentration than clopyralid. Both herbicides effluxed readily from the tissue after transfer to he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 32 publications
2
26
0
Order By: Relevance
“…Moreover, although the shoot Cu concentration was not reduced by chlorsulfuron, Cu concentration in roots was dramatically reduced. These observations are consistent with the facts that root entry of chlorsulfuron into cereal crops leads to a greater injury than foliar entry (Lemerle, 1993 and references therein) and that phloem transport of chlorsulfuron from leaves to roots is impaired (Devine et al, 1990). Zinc concentration in shoots, unlike Cu, was also reduced by chlorsulfuron.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, although the shoot Cu concentration was not reduced by chlorsulfuron, Cu concentration in roots was dramatically reduced. These observations are consistent with the facts that root entry of chlorsulfuron into cereal crops leads to a greater injury than foliar entry (Lemerle, 1993 and references therein) and that phloem transport of chlorsulfuron from leaves to roots is impaired (Devine et al, 1990). Zinc concentration in shoots, unlike Cu, was also reduced by chlorsulfuron.…”
Section: Discussionsupporting
confidence: 87%
“…In terms of penoxsulam, which is a foliage-translocated herbicide, some weeds escaped when it was applied at an early stage. Penoxsulam kill the weeds by inhibiting the acetolactase synthase enzyme, which ultimately reduced the transport of photosynthate from source leaves to roots, resulting in root growth inhibition (Devine, 1989;Devine, Bestman, & Vanden Born, 1990;Shaner, 1991). Because most of the weeds emerged late, they escaped the mechanism of transport of photosynthate from source leaves to roots.…”
Section: Yield Response and Weedsmentioning
confidence: 99%
“…Kleier (1988) developed a model demonstrating that weak acids, which exhibit intermediate permeability, are more likely to be translocated in the phloem with photosynthate. Devine et al (1990) found that translocation of sulfonylureas from treated leaves of common buckwheat (Fagopyrum tataricum L.) is limited by the availability of the branched-chain amino acids. A deficiency of these amino acids will cause the meristems to cease division, resulting in a loss of sink strength.…”
Section: Foliar Absorption and Translocationmentioning
confidence: 99%